The Development of Expert Systems Using Artificial Intelligence - A. Burnashev, Rustam; G. Gabdrahmanov, Ruslan; I. Enikeev, Arslan (International Journal of Psychosocial Rehabilitation, 2024)
This article presents a study related to the development of logical systems using artificial intelligence on the example of diagnosing leukemia. Data sets and logical rules that were used for the initial diagnosis of the disease were identified. In the process of learning, a neural network can reveal complex dependencies between the input data as well as summarize the information obtained. This system includes a perceptron and consists of 3 hidden layers: 80 neurons (relu), 40 neurons (selu), and 1 neuron (sigmoid). For software development, the programming language Python